A Legion of Lesions: The Neuroscientific Rout of Higher-Order Thought Theory. - Kozuch, Benjamin (Erkenntnis, 2024)
Higher-order thought (HOT) theory says that a mental state is conscious when and only when represented by a conceptual, belief-like mental state. Plausibly, HOT theory predicts the impairment of HOT-producing brain areas to cause significant deficits in consciousness. This means that HOT theory can be refuted by identifying those brain areas that are candidates for producing HOTs, then showing that damage to these areas never produces the expected deficits of consciousness. Building this refutation is a work-in-progress, with several key components of it already existing in the literature (e.g., Boly et al. in J Neurosci 37(40):9603–9613, 2017; Kozuch in Mind Lang, 37(5):790–813, 2022). This article pulls together and supplements these earlier components so as to provide a comprehensive lesion-based argument against HOT theory, one which offers extra data and arguments in support of it, and which also addresses common objections.